Effects of Hippocampal LIMK Inhibition on Memory Acquisition, Consolidation, Retrieval, Reconsolidation, and Extinction - Lunardi, Paula Santana (2018)
Long-lasting changes in dendritic spines provide a physical correlate for memory formation and persistence. LIM kinase (LIMK) plays a critical role in orchestrating dendritic actin dynamics during memory processing, since it is the convergent downstream target of both the Rac1/PAK and RhoA/ROCK pathways that in turn induce cofilin phosphorylation and prevent depolymerization of actin filaments. Here, using a potent LIMK inhibitor (BMS-5), we investigated the role of LIMK activity in the dorsal hippocampus during contextual fear memory in rats. We first found that post-training administration of BMS-5 impaired memory consolidation in a dose-dependent manner. Inhibiting LIMK before training also disrupted memory acquisition. We then demonstrated that hippocampal LIMK activity seems to be critical for memory retrieval and reconsolidation, since both processes were impaired by BMS-5 treatment. Contextual fear memory extinction, however, was not sensitive to the same treatment. In conclusion, our findings demonstrate that hippocampal LIMK activity plays an important role in memory acquisition, consolidation, retrieval, and reconsolidation during contextual fear conditioning.